A Discussion of the Clinical, Educational, and Social Impacts of Culturally Incongruent Speech-Language Professionals Who Serve African American English Speakers across Generations - Roberson-Middleton, Erica V. (Seminars in Speech and Language, 2025)
It is no secret that the overwhelming majority (91%) of certified speech-language pathologists (SLPs) identify as White, while Black SLPs make up less than 4% of the American Speech-Language-Hearing Association's (ASHA) member and affiliate profile (ASHA, 2022). On the other hand, Black students are disproportionately represented in special education programs (17%; NCES, 2024) and the majority (64%) qualify for services with speech-language (or related) diagnoses as of the 2022–2023 school year (NCES, 2024). These statistics suggest that Black students will likely encounter clinicians whose racial, cultural, and linguistic backgrounds differ from their own. Undoubtedly, the data have sparked conversations in the literature regarding the importance of cultural competence, cultural humility, and cultural sensitivity among therapists who serve racially and ethnically diverse clients. For instance, the discussion of SLPs' roles in addressing educational disparities for under-represented populations requires a level of self-awareness and cultural sensitivity that not every practitioner claims to possess. Further discussion regarding the pursuit of cultural competence is needed to contribute to a deeper understanding of clinical outcomes associated with cultural incongruence in SLPs.
Keywords: AAE; cultural congruence; generational differences; clinical outcomes